2010
DOI: 10.1007/s11606-010-1514-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Exercise and Dietary Behaviors of Middle-Aged and Older Adults

Abstract: BACKGROUNDDifferences in health behaviors may be important contributors to racial/ethnic disparities in the health status of adults. Studies to date have not compared whether there are health behavior differences in exercise and dietary behaviors among middle-age and older adults in the four largest racial/ethnic categories.OBJECTIVETo investigate racial/ethnic differences in exercise and dietary behaviors of middle-aged and older adults.DESIGNWe used data from the 2007 California Health Interview Survey. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 38 publications
(47 reference statements)
9
129
0
Order By: Relevance
“…These findings are consistent with recent studies which found associations between sedentary behavior and increased age, 35 being African American, 31 low level of education, 34 increased BMI, 34,43 and smoking. 34 The Hispanic group was less sedentary compared to non-Hispanic whites.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with recent studies which found associations between sedentary behavior and increased age, 35 being African American, 31 low level of education, 34 increased BMI, 34,43 and smoking. 34 The Hispanic group was less sedentary compared to non-Hispanic whites.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, multiple other analyses have confirmed lower prevalence of physical activity and healthy diet among race/ethnic minorities 19, 20. In addition to differences in weight perception, other barriers may be present that negatively impact these and other healthy lifestyle practices in minority groups.…”
Section: Discussionsupporting
confidence: 91%
“…We used participants' ratings of how many and how often they ate fruits or vegetables to assess the healthfulness of their food choices. A variable was derived to indicate frequency of daily fruit and vegetable consumption [55]. As guidelines suggest a minimum of five daily servings of fruits and vegetables for adults [52,55,56], the variable representing frequency of fruits and vegetables consumed per day was dichotomized (0 = ate \5 times per day, 1 = ate five or more times per day).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…A variable was derived to indicate frequency of daily fruit and vegetable consumption [55]. As guidelines suggest a minimum of five daily servings of fruits and vegetables for adults [52,55,56], the variable representing frequency of fruits and vegetables consumed per day was dichotomized (0 = ate \5 times per day, 1 = ate five or more times per day). Cardiovascular disease reduction guidelines also suggest B36 oz per week of sugar-sweetened beverages, such as soda [52].…”
Section: Outcome Variablesmentioning
confidence: 99%